Peer mentorship and transformational learning: PhD student experiences - Preston, Jane P.; Ogenchuk, Marcella J; Nsiah, Joseph K (Canadian Journal of Higher Education, 2014)
The purpose of the paper is to describe our peer mentorship experiences and explain how these experiences fostered transformational learning during our PhD graduate program in educational administration. As a literature backdrop, we discuss characteristics of traditional forms of mentorship and depict how our experiences of peer mentorship was unique. Through narrative inquiry, we present personal data and apply concepts of transformational learning theory to analyze our experiences. Our key finding was that it was the ambiguous boundaries combined with the formal structure of our graduate program that created an environment where peer mentorship thrived. We conclude that peer mentorship has great capacity to foster human and social capital within graduate programs for both local and international students.